Development of Authentic Assessment in Islamic Religious Education in Elementary School - Umi Baroroh; Tasman Hamani (Nazhruna: Jurnal Pendidikan Islam, 2022)
Assessment plays an important role in the educational process so there is a need for standardization of student education assessments. Permendikbud Number 23 of 2016 is an effort from the government to provide standards in the assessment of learning outcomes both carried out by the Education Unit and the Government. In the Permendikbud it is stated that the assessment of student learning outcomes includes three aspects, namely cognitive, affective, and psychomotor. The assessment of these three aspects in the 2013 curriculum is called authentic assessment. In practice, not all IRE (Islamic Religious Education) teachers apply authentic assessment. This study aims to elaborate on how IRE Elementary School teachers in Bantul District develop authentic assessments. This research is field research with a qualitative approach. The results of this study are the development of Authentic assessment conducted by IRE teachers in the Bantul sub-district consists of several development steps, namely first, observing or mapping KD (Basic competencies) and indicators to be tested. Second, determine the type of assessment that is tailored to the aspects to be tested. Third, compile an assessment that will be tested. Fourth, compose an answer key. Fifth, develop scoring guidelines. The recommendation from the results of this study is that in developing authentic assessments there should be simplifications related to testing trials in search of validity and reliability. This is because, at the level of implementation, this step is difficult for IRE teachers to implement.